Analysis of the Relationship Between Service Quality, Healthcare Facilities, Patient Satisfaction, and the Intention To Migrate BPJS Patients to Other Healthcare Facilities at Wonokusumo Health Center: Analisis Hubungan Antara Kualitas Layanan, Fasilitas Kesehatan, Kepuasan Pasien, dan Niat untuk Memindahkan Pasien BPJS ke Fasilitas Kesehatan Lain di Pusat Kesehatan Wonokusumo - Tri Puspitasari; Burhanudin; Basuki Rachmat (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
The increasing number of patient visits at the Wonokusumo Community Health Center demonstrates the importance of first-level healthcare facilities (FKTP) as the frontline of the National Health Insurance (JKN) service. Wonokusumo Community Health Center experienced a decline in patient satisfaction, leading to a desire to migrate to other healthcare facilities. This study aims to analyze the relationship between service quality and healthcare facilities on patient satisfaction and their impact on BPJS patient migration intentions. A quantitative approach was used with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The sample consisted of 252 BPJS patients using Maternity and Child Health (KIA) clinic services, selected using the purposive sampling technique. The results showed that service quality had a p-value of 0.003 and health facilities had a p-value of 0.007, both significantly influencing patient satisfaction, while patient satisfaction significantly influenced the desire to migrate with a p-value of 0.000. Health facilities and service quality did not significantly influence the desire to migrate for BPJS patients, with p-values of 0.161 and 0.101, respectively. This study provides important implications for the management of community health centers, focusing on improving service quality and facilities to maintain patient loyalty.